Sodium intake and Helicobacter pylori infection in the early stages of life - Monteiro, C (2016)
Introduction Helicobacter pylori infection is mainly acquired during childhood and is associated with an increased risk of developing gastric cancer. High amounts of sodium intake can lead to the onset of pre-malignant lesions contributing to the process of carcinogenesis, and potentiate the effect of H. pylori infection. This study aimed to evaluate the exposure to sodium in children until 4 years of age and to quantify its association with H. pylori infection. Methods This study includes 503 children from the cohort Generation XXI, recruited after childbirth and re-evaluated at 6 months and at 4 years of age. Information about socio-demographic characteristics, food intake after birth and status of H. pylori infection (assessed by serum ELISA) was collected. Scores of sodium exposure were calculated using the consumption of milk and other food items (evaluated at 6 months), and food items with the highest contribution to sodium intake and sodium intake (evaluated at 4 years). Logistic regression models were used to compute adjusted odds ratio (OR) and respective 95% confidence intervals (CI). Results We found that 28.2% of children were infected with H. pylori at 4 years of age, with a daily sodium intake that exceeded World Health Organization recommendations in 26%. No statistically significant association between sodium intake and H. pylori infection was observed, with the exception of the 2nd quarter in the score concerning consumption of “other food items” in the assessment at 6 months of age (OR = 2.41; 95%CI: 1.29–4.50). Conclusion No association between sodium intake and H. pylori infection was found; however, to the best of our knowledge, the present epidemiologic study is the first to test the influence of sodium intake in H. pylori infection in children.